Is there a relationship between hand grip strength and knee osteoarthritis in terms of radiological and functional findings in female patients? - Fazıl Kulaklı; İlker Fatih Sarı (Archives of Rheumatology, 2021)
Objectives: The aim of this study was to assess the presence of the relationship between hand grip strength (HGS) and radiological and functional signs of knee osteoarthritis (KOA). Patients and methods: Between March 2019 and January 2020, a total of 64 female patients (mean age: 63.4±8.8 years; range, 50 to 80 years) with bilateral chronic knee pain who were diagnosed with KOA using radiological and clinical findings according to the 2019 American College of Rheumatology guidelines were included in the study. Patient demographics, body mass index (BMI) values, and hand dominance were recorded. The Western Ontario and McMaster Universities Arthritis Index (WOMAC) and Lower Extremity Functional Scale (LEFS) were used for the assessment of KOA functionality. The Kellgren-Lawrence (KL) grading system was used for the radiological assessment of KOA. Electronic dynamometer was used for HGS measurement and values were normalized according to BMI results. Results: In the assessment of relationship between HGS and functionality of KOA, a negative, moderate correlation was found between the WOMAC and HGS-Dominant (D) (r=0.312, p<0.05) and HGS-Non-Dominant (ND) (r=0.391, p<0.01). In addition, a positive, moderate correlation was found between the LEFS and HGS-D (r=0.344, p<0.01) and HGS-ND (r=0.371, p<0.01). There was a weak, negative correlation between the HGS-ND, KL-D (r=0.256, p<0.05) and KL-ND (r=0.283, p<0.05), while no significant correlation was found between the HGS-D and KL. Conclusion: Our study results show that HGS-ND is associated with KOA radiologically and functionally. The HGS should be added in the WOMAC and LEFS scales in the functional assessment of KOA and new scales including HGS assessment should be developed.